2014
DOI: 10.1074/jbc.m114.563403
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the p75 Neurotrophin Receptor in Axonal Degeneration and Apoptosis Induced by Oxidative Stress

Abstract: Background:The p75 neurotrophin receptor (p75 NTR ) promotes neurodegeneration during development and in response to cellular injury. Results: Reactive oxygen species promoted cleavage of p75 NTR , leading to axonal degeneration and apoptosis. Conclusion: Oxidative stress activates intracellular p75 NTR signaling to induce neurodegeneration. Significance: These results suggest a novel mechanism through which p75 NTR contributes to neurodegeneration associated with cellular injury or pathological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 86 publications
4
35
0
Order By: Relevance
“…In our own experiments, we have not been able to detect significant changes in the proteolytic cleavage of p75 NTR in either HCNs or CGNs following NGF treatment (data not shown). Other studies have indicated that several other stimuli can influence the proteolytic processing of p75 NTR , including interaction with sortilin , ubiquitylation and palmitoylation (Powell et al, 2009;, activation of Trk receptors (Ceni et al, 2010;Kanning et al, 2003;Urra et al, 2007), myelin-derived ligands (Domeniconi et al, 2005), b-amyloid peptide (Sotthibundhu et al, 2008) and oxidative stress (Kraemer et al, 2014;Le Moan et al, 2011). Aside from its regulation, most studies are in agreement that proteolytic cleavage can affect p75 NTR -mediated signaling and biological activities.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In our own experiments, we have not been able to detect significant changes in the proteolytic cleavage of p75 NTR in either HCNs or CGNs following NGF treatment (data not shown). Other studies have indicated that several other stimuli can influence the proteolytic processing of p75 NTR , including interaction with sortilin , ubiquitylation and palmitoylation (Powell et al, 2009;, activation of Trk receptors (Ceni et al, 2010;Kanning et al, 2003;Urra et al, 2007), myelin-derived ligands (Domeniconi et al, 2005), b-amyloid peptide (Sotthibundhu et al, 2008) and oxidative stress (Kraemer et al, 2014;Le Moan et al, 2011). Aside from its regulation, most studies are in agreement that proteolytic cleavage can affect p75 NTR -mediated signaling and biological activities.…”
Section: Discussionsupporting
confidence: 51%
“…In order to assess the importance of proteolytic processing for the activities of p75 NTR in HCNs and CGNs, we first utilized a pharmacological approach based on selective inhibition of a-or c-cleavage with TAPI or DAPT, respectively. These compounds have previously been reported to effectively disrupt cleavage of p75 NTR in sympathetic neurons (Kenchappa et al, 2006;Kraemer et al, 2014), CGNs (Ceni et al, 2010) and HCNs (Volosin et al, 2008). Neither TAPI or DAPT were able to abolish NGF-induced activation of caspase-3 in HCNs (Fig.…”
Section: P75mentioning
confidence: 99%
See 1 more Smart Citation
“…CD271 was firstly isolated from a melanoma cell line and is expressed on neural crest cells from which melanocytes are derived (Kruger et al, 2002). It belongs to the TNF receptor superfamily and mediates apoptosis in different cell settings via its own signaling pathway (Kraemer et al, 2014;Truzzi et al, 2011;Blöchl and Blöch, 2007). The interaction of apoptosis related protein APR-1 with CD271 activate apoptosis in melanoma cells (Selimovic et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…In vitro studies have shown that reactive oxygen species (ROS) activate γ-secretase within the cell membrane, which in turn frees the intracellular domain of the p75 NTR for downstream signalling [61]. More recent studies demonstrate that this ligand-independent activation of p75 NTR s also results in axonal degeneration, at least in vitro [62]. Such a mechanism of p75 NTR activation is plausible in autoimmune diabetes because ROS is known to be generated in islets under autoimmune attack [63] (see also Fig.…”
Section: Mechanism Of Nerve Lossmentioning
confidence: 99%